Combinations of Methods for Collaborative Evaluation of the Usability of Interactive Software Systems - Andrés Solano; César A. Collazos; Cristian Rusu; Habib M. Fardoun (Advances in Human-Computer Interaction)
Usability is a fundamental quality characteristic for the success of an interactive system. It is a concept that includes a set of metrics and methods in order to obtain easy-to-learn and easy-to-use systems. Usability Evaluation Methods, UEM, are quite diverse; their application depends on variables such as costs, time availability, and human resources. A large number of UEM can be employed to assess interactive software systems, but questions arise when deciding which method and/or combination of methods gives more (relevant) information. We propose Collaborative Usability Evaluation Methods, CUEM, following the principles defined by the Collaboration Engineering. This paper analyzes a set of CUEM conducted on different interactive software systems. It proposes combinations of CUEM that provide more complete and comprehensive information about the usability of interactive software systems than those evaluation methods conducted independently.